Brief Reflections on Contract Scientificity - Solís Gózar, Julio (2015)
The main objective of this work is to demonstrate that the Legal Contract —a legal instrument, essential to our existence— as an institution of Civil Law, that enjoys all budgets to be considered as a Scientific Act, based on its features, its importance on the society and on the systematic and methodical evolution preceding to numerous studies that lead to determine principles and theories objectively supported.To demonstrate this proposal, is necessary the support of epistemology, philosophy, history, anthropology, sociology and comparative law in order to obtain a modest theoretical construction of its scientific line.